Encouraging Reading Habits in Children During the Pandemic through the Pekan Ceria Reading House Program - Wathon, Aminul; Wijayanti, Lulud (STAI Miftahul ULa Nganjuk, 2023)
The COVID-19 virus pandemic has greatly affected system changes in various fields, learning restrictions and the limited ability of teachers and parents to use gadgets have quite affected the character of children in Sukorejo, Drenges Village. To overcome this problem, the people of Sukorejo, especially RT 02 RW 17, made a reading house for a cheerful week. To get these asets, the author uses the Aset Based Community Development (ABCD) method, in addition to knowing that he is also able to design and develop existing asets and potential to further develop. During the mentoring process that Community Service Students carried out, there was an increase in reading interest in children in Sukorejo, especially RT 02 RW 17, in minimizing the use of gadgets during this pandemic.